Parental roles in developing creative thinking skills among secondary school students: A study in Sebha, Libya / Gadriya Omar Fidil Alsherif - Gadriya Omar, Fidil Alsherif (2017)
This study investigated the role of parents in the development of students’ creative thinking skills, specifically first year of secondary school students. The study was conducted to address this research question: to what extent the parents play role in improving the creative thinking skills for students? The study aimed at examining the effect of parents on enhancing students’ creative thinking skills. Not only this, but it sought to explore the factors that would influence the development of students’ creative thinking, find out parents’ direct reasons for developing students’ creative thinking skills, and determine the educational practical solutions to solve parents’ deficiency in promoting students’ creative thinking skills. This descriptive study adopted a social survey method. It was carried out with some student adults in the first year of their secondary school in Sebha, Libya. The sample of the study consisted of (340) respondents. Out of this number, there were (239) fathers (70.3%) and (101) mothers (29.7%). Data was collected through a questionnaire. Descriptive analysis as well as some statistical tests were run to analyse the obtained data including ANOVA, T test and Spearman correlation coefficient. Findings indicated that parents did have an impact on the enhancement of students’ creative thinking skills which was ascribed to some variables such as housing type, family size, and social situation which could be due to financial, economic and social factors. The most important factors affecting the development of students’ creative thinking were: level of education, family income, family bond, caring, parents’ continuous guiding to their children, family size, and gender. Parents’ direct concerns for developing students’ creative thinking were related to parents’ educational level and income, family size and bond, and parents’ care to follow up their children. Findings emerged from statistical analysis uncovered that educational solutions could be in the provision of suitable housing, caring more about family bond, having stable social status, availability of facilities that increase creativity, having a good income, and improvement of parents’ educational level The nature of the study and the inclusion of theoretical and practical aspects hindered the researcher from maintaining abalance of the page numbers of each chapter.